Gold nanoparticles embedded in a polymer as a 3D-printable dichroic nanocomposite material - Kool, Lars; Bunschoten, Anton; Velders, Aldrik H.; Saggiomo, Vittorio (Beilstein Journal of Nanotechnology, 2019)
Background: Nanotechnology, even if unknowingly, has been used for millennia. The occurrence of shiny colors in pottery and glass made hundreds and thousand of years ago is due to the presence of nanoparticles in the fabrication of such ornaments. In the last decade, 3D printing has revolutionized fabrication and manufacturing processes, making it easier to produce, in a simple and fast way, 3D objects.Results: In this paper we show how to fabricate a 3D-printable nanocomposite composed of dichroic gold nanoparticles and a 3D-printable polymer. The minute amount of gold nanoparticles used for obtaining the dichroic effect does not influence the mechanical properties of the polymer nor its printability. Thus, the nanocomposite can be easily 3D-printed using a standard 3D printer and shows a purple color in transmission and a brownish color in reflection.Conclusion: This methodology can be used not only by artists, but also for studying the optical properties of nanoparticles or, for example, for the 3D fabrication of optical filters.
Keywords: 3D printing; dichroism; gold nanoparticles; nanocomposite

(untitled) - Chalmin, E.; Menu, M.; Vignaud, C. (Meas. Sci. Technol., 2003)

(untitled) - Brun, N.; Mazerolles, L.; Pernot, M. (J. Mater. Sci. Lett., 1991)

(untitled) - Faraday, M. (Philos. Trans. R. Soc. London, 1857)

(untitled) - Heiligtag, F. J.; Niederberger, M. (Mater. Today, 2013)

The Delivery of Nanoparticles - Sciau, P. (Nanoparticles in Ancient Materials: The Metallic Lustre Decorations of Medieval Ceramics, 2012)

Optical Technologies in the Humanities - Horn, I.; von Kerssenbrock-Krosigk, D.; Schulz, G.; Syndram, D. (Ruby Glass of the Baroque Period: An Interdisciplinary Study, 1997)

(untitled) - Freestone, I.; Meeks, N.; Sax, M.; Higgitt, C. (Gold Bull., 2007)

7th International Congres of Glass - Brill, R. H. (The chemistry of the Lycurgus Cup, 1965)

(untitled) - Barber, D.; Freestone, I. C. (Archaeometry, 1990)

(untitled) - Manzano, J. S.; Weinstein, Z. B.; Sadow, A. D.; Slowing, I. I. (ACS Catal., 2017)

(untitled) - Skorski, M. R.; Esenther, J. M.; Ahmed, Z.; Miller, A. E.; Hartings, M. R. (Sci. Technol. Adv. Mater., 2016)

(untitled) - Turkevich, J.; Stevenson, P. C.; Hillier, J. (Discuss. Faraday Soc., 1951)

(untitled) - Shi, L.; Buhler, E.; Boué, F.; Carn, F. (J. Colloid Interface Sci., 2017)

(untitled) - Liz-Marzán, L. M. (Mater. Today, 2004)

(untitled) - Huang, X.; El-Sayed, M. A. (J. Adv. Res., 2010)

(untitled) - Som, T.; Karmakar, B. (Plasmonics, 2010)

(untitled) - Magruder, R. H., III; Robinson, S. J.; Smith, C.; Meldrum, A.; Halabica, A.; Haglund, R. F., Jr (J. Appl. Phys., 2009)

(untitled) - Pei, L.; Mori, K.; Adachi, M. (Langmuir, 2004)

(untitled) - Ji, X.; Song, X.; Li, J.; Bai, Y.; Yang, W.; Peng, X. (J. Am. Chem. Soc., 2007)

(untitled) - Longenberger, L.; Mills, G. (J. Phys. Chem., 1995)

Natural and Synthetic Biomedical Polymers - Subramaniam, A.; Sethuraman, S. (Biomedical Applications of Nondegradable Polymers, 2014)